Comparison of calcium carbonate and titania particles on improving color homogeneity and luminous flux of WLEDs - Thinh Cong Tran; Nguyen Doan Quoc Anh; Nguyen Thi Phuong Loan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In this paper, the experiments on phosphor-converted LEDs (pc-LEDs) with a correlated color temperature (CCT) of 8500K has been conducted with the scattering enhancement particles (SEPs) to achieve the higher color uniformity and emitted luminous flux of pc-LEDs. Moreover, this paper also introduced about choosing scattering enhancement particles (SEPs), including calcium carbonate (CaCO3) and titania (TiO2), and compared these particles’ properties by adding them into the yellow Y3Al5O12:Ce3+ phosphor compounding. Afterward, the LightTools program was applied to illustrate the optical simulation, and obtained results was analyzed and verified by applying the Mie-scattering theory. The scattering coefficients, the anisotropic scattering, the reduced scattering, and the scattering amplitudes at 455 nm and 595 nm are included in the scattering computation of SEPs. According to researched results, among the SEPs, TiO2 particles result in the highest value of color uniformity. However, a rise in their concentration is the cause of a sharp decline in luminous flux. Meanwhile, CaCO3 particles show the ability of reducing the deviated level in correlated color temperature by 620K if there is employed 30% of CaCO3 concentration. Hence, CaCO3 particles are the recommendation for achieving higher chromatic homogeneity and lumen output.